Hadoop : the definitive guide - White, Tom. (Beijing ; Sebastopol, CA : O'Reilly, 2009)
Organizations large and small are adopting Apache Hadoop to deal with huge application datasets. This guide provides you with the key for unlocking the wealth this data holds. It demonstrates how to use Hadoop to build reliable, scalable, distributed systems.
"MapReduce for the cloud"--Cover.
"Yahoo! Press"--Cover.
Includes index.
Keywords: Apache Hadoop (Computer file); Electronic data processing -- Distributed processing; File organization (Computer science); Cloud computing